REGULATION OF CHEMICAL WEAPONS IN SELF-DEFENSE UNDER ARTICLE 51 OF THE UNITED NATIONS CHARTER - Faradilla, Rizka; Adwani, Adwani (Universitas Syiah Kuala, 2024)
This study examines the regulation and use of chemical weapons in the context of state self-defense, exploring why certain countries resort to chemical weapons to defend against attacks. Conducted as normative legal research, the findings reveal that Article 51 of the United Nations Charter, which addresses self-defense, does not explicitly outline permissible weapons for this purpose. Consequently, many countries continue to utilize chemical weapons, despite their prohibition in warfare. The United Nations should consider amending the Charter, particularly Article 51, to include clearer guidelines on anticipatory self-defense actions. This would help prevent nations from justifying armed attacks for self-serving interests that ultimately harm others.